Role of Keratinocytes in Sensitive Skin - Talagas, Matthieu; Misery, Laurent (Frontiers in Medicine, 2019)
Sensitive skin is a clinical syndrome defined by the occurrence of unpleasant sensations such as burning, stinging, tingling, pricking or itching in response to various normally innocuous physical, chemical and thermal stimuli. These particular symptoms have led the consideration of a potential dysfunction of the intra-epidermal nerve fibers that are responsible for pain, temperature and itch perception. This neuronal hypothesis has just been reinforced by recent studies suggesting that sensitive skin could become assimilated to small fiber neuropathy. Meanwhile, the involvement of keratinocytes, the predominant epidermal cell type, has so far mainly been considered because of their role in the epidermal barrier. However, keratinocytes also express diverse sensory receptors present on sensory neurons, such as receptors of the transient receptor potential (TRP) family, including Transient Receptor Potential Vallinoid 1 (TRPV1), one of the main transducers of painful heat which is also involved in itch transduction, and Transient Receptor Potential Vallinoid 4 (TRPV4) which is depicted as a heat sensor. While TRPV1 and TRPV4 are expressed both by sensory neurons and keratinocytes, it has recently been demonstrated that the specific and selective activation of TRPV1 on keratinocytes is sufficient to induce pain. Similarly, the targeted activation of keratinocyte-expressed TRPV4 elicits itch and the resulting scratching behavior. So, contrary to classical conception, the intra-epidermal nerve fibers are not the exclusive transducers of pain and itch. In light of these recent advances, this review proposes to consider the putative role of epidermal keratinocytes in the generation of the unpleasant sensations characteristic of sensitive skin syndrome.